2022
DOI: 10.3390/ijms232113645
|View full text |Cite
|
Sign up to set email alerts
|

EMT Molecular Signatures of Pancreatic Neuroendocrine Neoplasms

Abstract: Neuroendocrine neoplasms (NENs) are relatively rare neoplasms occurring predominantly in the gastrointestinal tract and pancreas. Their heterogeneity poses challenges for diagnosis and treatment. There is a paucity of markers for characterisation of NEN tumours. For routine diagnosis, immunohistochemistry of the NEN-specific markers CgA and synaptophysin and the proliferation marker Ki-67 are used. These parameters, however, are qualitative and lack the capacity to fully define the tumour phenotype. Molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The contribution of DAXX in pancreatic neuroendocrine tumors (PanNETs) is undoubtedly among the most extensively studied. While it has been the subject of a considerable number of studies, no contradictory results have been reported, with researchers agreeing on the overall tumor-promoting role of DAXX loss in pancreas tumorigenesis [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69].…”
Section: Pancreasmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of DAXX in pancreatic neuroendocrine tumors (PanNETs) is undoubtedly among the most extensively studied. While it has been the subject of a considerable number of studies, no contradictory results have been reported, with researchers agreeing on the overall tumor-promoting role of DAXX loss in pancreas tumorigenesis [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69].…”
Section: Pancreasmentioning
confidence: 99%
“…In contrast, G3 samples exhibited higher DAXX mRNA expression in tumor tissues relative to non-tumorous ones. Additionally, DAXX IHC staining was absent in non-tumor, G1 and G2 tumor tissues, while strong nuclear staining was observed in less than 25% of cells in G3 tumor tissues [56]. DAXX mutation was identified in 13 out of 51 cases (25%) of 51 neuroendocrine liver metastases specimens, and the presence of DAXX mutation was associated with shorter hepatic progression-free survival (PFS) [57].…”
Section: Pancreasmentioning
confidence: 99%